Lipid peroxidation of immune cells in cancer - Xiao, Liuling; Xian, Miao; Zhang, Chuanchao; Guo, Qi; Yi, Qing (Frontiers in Immunology, 2024)
Growing evidence indicates that cellular metabolism is a critical determinant of immune cell viability and function in antitumor immunity and lipid metabolism is important for immune cell activation and adaptation to the tumor microenvironment (TME). Lipid peroxidation is a process in which oxidants attack lipid-containing carbon-carbon double bonds and is an important part of lipid metabolism. In the past decades, studies have shown that lipid peroxidation participates in signal transduction to control cell proliferation, differentiation, and cell death, which is essential for cell function execution and human health. More importantly, recent studies have shown that lipid peroxidation affects immune cell function to modulate tumor immunity and antitumor ability. In this review, we briefly overview the effect of lipid peroxidation on the adaptive and innate immune cell activation and function in TME and discuss the effectiveness and sensitivity of the antitumor ability of immune cells by regulating lipid peroxidation.